PELAYANANKESEHATAN PEDULIREMAJA (PKPR) DALAMMENINGKATKAN PHBSPADA SANTRIDI PONDOKPESANTREN SHOFAMARWA - Kustin Hariyono (Jurnal Kesehatan, 2021)
Adolescence is a vulnerable period because this period is a time forthem to find their identity.This is the time we need to pay attention to. One manifestation of the government's concernfor youth to become a quality generation through the Ministry of Health is to promote theAdolescent Health Care Services (Pelayanan Kesehatan Peduli Remaja) . These programsinclude counseling, clinical services and counseling by program implementers, as well astraining peer counselors. Peer counselors in question are adolescent health cadres who havebeen given additional training in interpersonal relationships and counseling. This programcan be applied to students to create clean living behavior for students in Islamic boardingschools. The purpose of the study was to detremine the effectiveness of adolescent healthcadrea in improving PKPR (Adolescent Care Health Services) behaviour in Santri at theShofa Marwa Islamic Boarding School, Jember Regency.This research was quantitative witha quasi-experimental research design with a one group pre-test-post-test design approach.The population was students with a sample of 50. Clean and Healthy Life Behavior ofstudents before the Adolescent Care Health Service is in good criteria by 10% and after theAdolescent Care Health Service was formed there was an increase in good criteria to 60%.There was a significant change in the Clean and Healthy Lifestyle of the santri before andafter the Adolescent Care Health Service was established. P=0.000<α 0.05. It is hoped thatthe Islamic boarding school can continue to monitor this activity so that the Clean andHealthy Life Behavior of students can continue to be improved.